2021
DOI: 10.1590/0034-737x202168050003
|View full text |Cite
|
Sign up to set email alerts
|

Jambu varieties performance under shading screens

Abstract: Shading screens have been extensively used in leafy-vegetables production system. Nevertheless, there is still a substantial lack of knowledge regarding the effects of this technology on the performance of non-conventional vegetables such as jambu, a typical staple food with social and economic importance for the Amazon region. This study thus aimed to evaluate the effects of shading screens on the agronomic performance of two jambu varieties. The experiment was performed in a randomized block design, in a 4 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…We expect significant differences when it comes to analyzing the leaf development in relation to shading (Llic & Fallik, 2017), nevertheless some vegetables presented different behaviors. Some studies, which were carried out by Ferreira et al (2021), on shading on jambu plants (Acmella oleracea), which is also an unconventional vegetable, showed that the shading screens had not provided significant differences for leaf area considering the evaluated varieties. The same was observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…We expect significant differences when it comes to analyzing the leaf development in relation to shading (Llic & Fallik, 2017), nevertheless some vegetables presented different behaviors. Some studies, which were carried out by Ferreira et al (2021), on shading on jambu plants (Acmella oleracea), which is also an unconventional vegetable, showed that the shading screens had not provided significant differences for leaf area considering the evaluated varieties. The same was observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Jambu (Acmella oleracea (L.) R. K. Jansen) is a non-conventional herbaceous vegetable with small size and branching creeping stems, belonging to the Asteraceae family. It is consumed in typical dishes of the Northern region of Brazil and used for medicinal purposes (Gusmão & Gusmão, 2013;Ferreira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…O jambu apresenta propriedades culinárias e medicinais, sendo utilizado na gastronomia (NEVES et al, 2019), na medicina popular (FERREIRA et al, 2021;OLIVEIRA BRITO et al, 2022) e como inseticida (ARAÚJO et al, 2018). Na culinária, o jambu é utilizado no prato paraense tradicional chamado tacacá, uma sopa quente que combina tucupi (caldo extraído da mandioca), camarão, goma de mandioca e jambu (HOMMA et al, 2011).…”
Section: Introductionunclassified